(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article presents the risks of intimate communication on the Internet and counteraction to sexting under the legislation of the Republic of Poland. The level of theoretical development of the risks of intimate communication in the legislation of the Republic of Poland is determined. The author also identifies the most common threats caused by the phenomenon of sexting and formulates a position on the need to fill in the theoretical knowledge in the field of counteracting the risks of intimate communication on the Internet.